As good as it gets?: Stateness and democracy in East Timor - Croissant, Aurel; Sharkh, Rebecca Abu (Stateness and democracy in East Asia, 2020)
The chapter analyses the simultaneous state-building and democratization process in East Asia’s newest sovereign nation-state. Since 2002, East Timor has strived to create a democratic and effective state out of the ashes of colonial rule, armed conflict and foreign occupation. With the assistance of the United Nations (UN), East Timor has thus undergone a process of simultaneous state and democracy building. Despite tremendous challenges, democracy has been surprisingly resilient against a number of severe crises. East Timor thereby represents a highly unusual mix of a fragile stateness but, given the circumstances, a relatively resilient (though, low-quality) democracy. This chapter investigates the reasons for and the implications of this surprising combination. In so doing, the chapter demonstrates that democratization and democracy have contributed to further consolidation of nation-building and statehood in East Timor. At the same time, however, limited stateness is one of the main reasons why democracy remains of low quality.
Gesehen am 20.04.2021